(3EfSGf GdYjhf aj eTGgjQ SGOS GdbQhfs - (3TgGH GdOjf CMeO Hf eMeO Hf YeQ GdebOSj GdTGaYj, GHf CHj YPjHI,J (B856 (3g` s
(3ChdgG (B:s
(3PcQ NdGaI GdfGUQ dOjf Gddg CHj GdYHGS CMeO Hf GdeSJVF s
(3BNQgG (B:s
(3ahbY GdbJGd hcGOhG jXaQhf HCejQ GdMGL , aTb GdfGUQ GdUaha hcde GdCejQ ai PcQ CNHGQ GdfGUQ Hf OGhO Hf Gdedc GdYGOd YjSi Hf eMeO Hf CjhH s
(3ai UOQ GdfSNI Cf GdCSJGP chQcjS YhGO GfJgi Edi Gf gPG GdcJGH bWYI ef JGQjN Ohd GdCYjGf hCf JGQjN GdCYjGf efg fSNI ai NRGfI GdCSJGP YHGS GdZRGhi HHZOGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B228s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B54 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI HZOGO (B(248) s
Keywords: (3GdJGQjNs